2015
DOI: 10.1902/jop.2015.140698
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Analysis of Association Between Interleukin‐1β C‐511T Polymorphism and Chronic Periodontitis Susceptibility

Abstract: Based on currently available evidence, IL-1β C-511T polymorphism is not associated with the risk of developing CP. Additional research is warranted to further explore and confirm the association of genetic polymorphism and CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 50 publications
2
46
0
1
Order By: Relevance
“…Furthermore, in another meta-analysis conducted by Zeng et al (2015), two of the studies (Loo et al, 2012;Hao et al, 2013) potentially involved the same subjects of the Chinese population. The present meta-analysis was strengthened by the exclusion of duplicated studies, and significant results were revealed in the subgroup and overall analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in another meta-analysis conducted by Zeng et al (2015), two of the studies (Loo et al, 2012;Hao et al, 2013) potentially involved the same subjects of the Chinese population. The present meta-analysis was strengthened by the exclusion of duplicated studies, and significant results were revealed in the subgroup and overall analyses.…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were conducted using the Comprehensive Meta-Analysis v2.2 software (Zeng et al, 2015b). The ORs and its 95%CIs were used to evaluate the pooled and single effect size to determine whether there was a significant association between cases and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analysis was performed to investigate the influence of a single study on overall analysis, and to test the robustness of overall results. Potential publication bias was assessed by visual inspection of funnel plots and the Egger test (Mao et al, 2013;Zeng et al, 2015b). Five genetic models were used for overall and subgroup analyses (Suo et al, 2015;Zeng et al, 2015b): A vs G, AA vs GG, AG vs GG, (AG+AA) vs GG, and AA vs (AG+GG).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, different studies have failed to establish an association of the IL1B -511C>T polymorphism with the development of AgP and/or CP. [32729] However, in a meta-analysis, a weak association between this polymorphism and CP was observed, with the T allele representing a risk for the disease, especially among Asians. [30]…”
Section: Discussionmentioning
confidence: 99%